A new structure–activity relationship for cyanine dyes to improve photostability and fluorescence properties for live cell imaging. Issue 31 (12th July 2018) - Schwechheimer, Christian; Rönicke, Franziska; Schepers, Ute; Wagenknecht, Hans-Achim
Abstract : A new set of cyanine-indole dyes was synthesized, characterized by optical and cytotoxic properties and subsequently applied for live cell imaging. Abstract : A new set of cyanine-indole dyes was synthesized, characterized by optical and cytotoxic properties and subsequently applied for live cell imaging. Furthermore, these dyes were postsynthetically linked covalently to the 2′-position of uridine anchors in presynthesized oligonucleotides using the copper(i )-catalyzed azide–alkyne cycloaddition in order to evaluate their photostability and imaging properties in living cells. The nucleophilicity at position C-2 of the indole part of the dyes was elucidated as key for a new structure–activity relationship that served as a rational guide to improve the photostability and optical properties of these green-emitting dyes for live cell imaging of nucleic acids. While the photostability rises exponentially with decreasing nucleophilicity, thermal bleaching experiments confirmed an opposite trend supposing that the superoxide radical anion is mainly responsible for the photobleaching of the dyes. Furthermore, the cytotoxicities of the dyes were tested in HeLa cells and moderate to low LD50 values were obtained. This interdisciplinary strategy allowed us to identify one dye with excellent optical properties and even better photostability and decreased cytotoxicity compared to a cyanine-indole dye that bears an additional cyclooctatetraene group as a triplet state quencher.